-21-9h=-3(4h+5)

Simple and best practice solution for -21-9h=-3(4h+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -21-9h=-3(4h+5) equation:


Simplifying
-21 + -9h = -3(4h + 5)

Reorder the terms:
-21 + -9h = -3(5 + 4h)
-21 + -9h = (5 * -3 + 4h * -3)
-21 + -9h = (-15 + -12h)

Solving
-21 + -9h = -15 + -12h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '12h' to each side of the equation.
-21 + -9h + 12h = -15 + -12h + 12h

Combine like terms: -9h + 12h = 3h
-21 + 3h = -15 + -12h + 12h

Combine like terms: -12h + 12h = 0
-21 + 3h = -15 + 0
-21 + 3h = -15

Add '21' to each side of the equation.
-21 + 21 + 3h = -15 + 21

Combine like terms: -21 + 21 = 0
0 + 3h = -15 + 21
3h = -15 + 21

Combine like terms: -15 + 21 = 6
3h = 6

Divide each side by '3'.
h = 2

Simplifying
h = 2

See similar equations:

| [7+(-3)]+(-5)=7+[(-3)+(-5)] | | 30-7m+10-3m= | | 2x+2*2x+7=2x+7 | | -21-9h= | | (X+28)=(3x+14) | | 260-64-9= | | (2/7)÷N=(5/7) | | 9.8k+3.7=-0.22 | | a^2-4a+4-b^2= | | y=3e^5x | | 3/4(x-6)=2/8(x+2) | | y^2-16x-64=0 | | 38*x^3+19x^2-158=0 | | R=D-TforD | | .5x-2=.3x+1.2 | | -4c+3-6c=34 | | -x+4x=40 | | 2log(x-5)=6 | | Z/12=12/4 | | X/12=59/60 | | y=-3x^2-6(3)-5 | | 3/w=18/42 | | x^2+4m-12=0 | | N-3=20/8 | | 6x+2=4-(2x-5) | | n^3-n^2=6n | | 4-5+7-4k=0 | | x+16=2x-24 | | 5t-3t=18+3(1-t) | | 2xy=x-3y | | 16-w=72 | | 7+3k-2=4 |

Equations solver categories